Optimization of high quality total RNA isolation from the microalga, Chlorella sp. (Trebouxiophyceae, Chlorophyta) for next‐generation sequencing. Issue 2 (12th January 2017) - Poong, Sze‐Wan; Lim, Phaik‐Eem; Lai, Jeannette W.‐S.; Phang, Siew‐Moi
SUMMARY: The advent of high‐throughput next‐generation sequencing (NGS) has enabled more comprehensive transcriptome analyses to obtain gene expression data and understand metabolic pathways essential for functional analysis and systems biology. The isolation of high purity and intact RNA of sufficient quality and yield is crucial to the success of NGS sequencing. In green microalgae, extraction of nucleic acids is hindered by high concentration of lipids and polysaccharides that co‐precipitate with nucleic acids thus resulting in reduced yield and poor quality extracts. The present study compared the performance of standard and modified total RNA isolation protocols using different cell disruption techniques combined with TRIzol reagent or a commercially available kit, in meeting the stringent requirements for downstream NGS application of a green freshwater microalga, Chlorella sp. The protocols were evaluated for (i) the yield of RNA, (ii) integrity of RNA as determined by the RNA integrity number and (iii) the purity of RNA as determined by the A260 /A280 and A260 /A230 ratios. In general, higher yields were obtained by cell disruption via flash freezing and homogenizing with liquid nitrogen followed by lysis with TRIzol reagent. We recommend the incorporation of a salt precipitation step to improve the purity and integrity of RNA isolated. Results of this study served as a simple and low‐cost practical guide for researchers working on isolation of high quality total RNA from microalgae, considering that most relevant publications do not provide a detailed methodology for total RNA isolation or use more expensive methods (e.g. bead‐beater).